2019
DOI: 10.1016/j.proci.2018.07.075
|View full text |Cite
|
Sign up to set email alerts
|

Three-stage heat release in n-heptane auto-ignition

Abstract: Colloquium: REACTION KINETICS / INTERNAL COMBUSTION ENGINES Word Count (Method 1): The total word count (exclusive of title page, abstract) is: 5793 words Word Count (Performed from automatic counting function in MS Word plus References/Tables/Equations/ Figures) Abstract: 235 words, not included in word count Equations: 0 words (0 equations, single column) Figures: 1030 words (4 figures with captions) 3 single 50(+10) 132 4 double 52(+10) 273 Captions 116 Total: 6055 words Supplemental Materials: One suppleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
51
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(60 citation statements)
references
References 37 publications
9
51
0
Order By: Relevance
“…On the other hand, when the temperature is pointed strongly, then the system undergoes the thermal runaway, which usually develops in the last part of the explosive stage [22,29,42]. In previous studies relating to the autoignition of H 2 /air, CH 4 /air, n-hexane/air, n-heptane/air, DME/air, and ethanol/air mixtures, it was shown that chemical runaway regime practically occupies all the explosive stage, while the thermal runaway regime only appears at the very final portion of the explosive stage [22,34,37,38,41,43,44,46,[52][53][54][55][56]. The results diaplayed in Table 2 suggest that autoignition of ammonia is qualitatively different than this of hydrocarbons in that the chemical runaway process is very short and the process develops as a thermal explosion.…”
Section: Autoignition Of Ammoniamentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, when the temperature is pointed strongly, then the system undergoes the thermal runaway, which usually develops in the last part of the explosive stage [22,29,42]. In previous studies relating to the autoignition of H 2 /air, CH 4 /air, n-hexane/air, n-heptane/air, DME/air, and ethanol/air mixtures, it was shown that chemical runaway regime practically occupies all the explosive stage, while the thermal runaway regime only appears at the very final portion of the explosive stage [22,34,37,38,41,43,44,46,[52][53][54][55][56]. The results diaplayed in Table 2 suggest that autoignition of ammonia is qualitatively different than this of hydrocarbons in that the chemical runaway process is very short and the process develops as a thermal explosion.…”
Section: Autoignition Of Ammoniamentioning
confidence: 99%
“…Note that the point where the two time scales meet is right before the point where the temperature completes its steep increase. This feature appears also in the autoignition of H 2 /air, CH 4 /air, n-hexane/air, n-heptane/air, DME/air, and ethanol/air mixtures [22,34,37,38,41,43,44,46,[52][53][54][55][56].…”
Section: Autoignition Of Ammoniamentioning
confidence: 99%
“…As indicated in the figure, almost all timescales at any given instance are dissipative (indicated by solid curves) and very few are explosive (indicated in dotted curves). This is a common feature of the homogeneous autoignition process that has been demonstrated extensively; e.g., [41,42,46,47,[59][60][61][62][63][64][65][66][67][68]. The few explosive timescales appear from the start of the process until the point where the temperature undergoes a steep increase.…”
Section: Csp Analysis On Auto-ignition Systemsmentioning
confidence: 83%
“…The system of the M algebraic equations ( f m ≈ 0) defines a low dimensional surface, known as slow invariant manifold (SIM), on which the solution evolves, while the system of ordinary differential equations (ODEs) governs the slow evolution of the solution on the SIM and its dynamics is characterized by the fastest of the slow time scales (M + 1), when the solution evolves sufficiently far from the boundaries of the SIM [29]. The identification of the slow characteristic CSP mode (i.e., the M + 1 mode) can be achieved only in the context of a reduced model, where the fast and slow modes can be well-defined [30][31][32][33][34]. The sign of the real part of the eigenvalue associated with each mode determines the mode's nature: a positive or negative real part indicates an explosive or dissipative mode, respectively.…”
Section: Computational Singular Perturbation (Csp) Algorithmic Tmentioning
confidence: 99%